Examining the interplay between endometriosis and later-life cerebro-cardiovascular diseases: A systematic review, meta-analysis, and trial sequential analysis - Winata, I GS.; Immanuel, Surya S.; Leonardo, Leonardo; Rinaldi, Fransiskus X.; Tandecxi , Gabriel; Wijaya, Richard (Narra Sains Indonesia, 2025)
Beyond gynecological issues, women with endometriosis have a significant risk of cardiac outcomes. Despite this evidence, the extent and mechanisms of the association remain unclear. The aim of this study was to evaluate the association between endometriosis and the incidence of cerebro-cardiovascular disorders. Using preferred reporting items for systematic review and meta-analyses (PRISMA) guidelines, seven databases were searched as of October 14, 2024, for observational studies assessing the association between endometriosis and cerebro-cardiovascular disorders. The main outcome was major adverse cardiovascular and cerebrovascular event (MACCE) while the secondary outcomes included all-cause mortality, cerebrovascular accident (CVA), ischemic heart disease (IHD), myocardial infarction (MI), arrhythmia, and heart failure (HF). Bias was assessed with the risk of bias in non-randomized studies of exposures (ROBINS-E) tool. Odds ratios with 95% confidence interval (CI) were calculated using random-effects meta-analysis. Evidence certainty was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Robustness was assessed via sensitivity analyses and trial sequential analysis (TSA). Out of 3,141 studies, nine cohort studies encompassing 1,670,589 women (follow-up 7–28 years) were included. Endometriosis was associated with 24% higher odds of MACCE incidence (95%CI: 1.18–1.31, moderate certainty). In addition, having endometriosis increased the odds of CVA by 49% (95%CI: 1.20–1.85, high certainty), IHD by 64% (95%CI: 1.31–2.05, low certainty), MI by 53% (95%CI: 1.18–1.98, high certainty), arrhythmias by 24% (95%CI: 1.12–1.37, high certainty), and HF by 13% (95%CI: 1.03–1.25, high certainty). Endometriosis did not significantly associate with all-cause mortality. Sensitivity analyses and TSA reinforced all of these findings. In conclusion, endometriosis was significantly associated with increased odds of cerebro-cardiovascular disorders. Future research should clarify the underlying mechanisms and develop targeted prevention strategies.